Efek Ekstrak Etanol Herba Bandotan (Ageratum conyzoides, L.) terhadap Waktu Perdarahan dan Pembekuan Darah pada Tikus Putih Jantan (Rattus norvegicus) - Santie Apriyani; Titik Sunarni; Dwi Ningsih (Fakultas Farmasi Universitas Setia Budi, 2011)
The aim of this experiment was to find out the effect of Bandotan (Ageratum conyzoides, L) herbs ethanol extract that given orally on decreasing bleeding and blood coagulation time in white male rats (Rattus norvegicus) wistar strain. Bandotan herbs were extracted by soxhlet using 70% ethanol as solvent. The animals test were divided in five groups, each group consist of 5 mice. Group I was given dose 69,58 mg, group II was given dose 104,37 mg, and group III was given dose 139,16 mg/200 g BW. Group IV as positive control was given tranexamic acid 4,5 mg/200 g BW. Group V as negative control was given CMC 1%. The animals test were given sub cutaneous heparin injection for 5 days to induce bleeding and inhibit blood coagulation, and then were given test preparation for 6 days and the time of bleeding ceasing and blood coagulation were recorded once every 2 days during test preparation was given. statistic results of the study showed that ethanol extract of goat weed herbs given orally could decrease bleeding time and blood coagulation in white male rats. According to the result of two ways anova statistical test, ethanol extract of goat weed herbs with dose of 104,37 mg/200 g BW is effectivest in decreased bleeding and blood coagulation time with ability to stop bleeding time 85,45% and blood coagulation time 70%.